Istory of development and the current state of foreign trade between the Republic of Korea and Uzbekistan - Talipova, Nigora (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
The Republic of Uzbekistan and the Republic of Korea are bound by traditional relations of friendship and cooperation based onuniversally recognized principles and norms of international law. Both countries pay great attention to issues of bilateral cooperation in the political, economic, cultural and other fields. The article is dedicated to the successful development of bilateral relations in all areas, which is facilitated by the absence of any political problems between the countries and a solid legal base